Clinical imaging of primary pulmonary nucleoprotein of the testis carcinoma - Huang, Wenpeng; Zhang, Yongbai; Yang, Qi; Gao, Ge; Qiu, Yongkang; Li, Liming; Kang, Lei (Frontiers in Medicine, 2023)
Primary pulmonary nucleoprotein of the testis (NUT) carcinoma is very rare in clinic. In this study, the clinicopathological manifestations and imaging features of the primary pulmonary NUT carcinoma were investigated to improve the diagnosis of this disease. 6 patients with pathologically diagnosed pulmonary NUT carcinoma were analyzed, Most of the patients with pulmonary NUT carcinomas presented as heterogeneous lobulated masses, four cases were located in the upper lobe of the left lung, one case in the middle lobe of the right lung, and one case in the lower lobe of the right lung, with the maximum diameter ranging from 1.30 to 8.90 cm and the median of 3.55 cm, most of them were irregularly shaped, with more lobulated margins and more heterogeneous density (83.33%), and the enhancement was mild. PET/CT showed increased 18F-FDG uptake in the lesion and metastatic areas and the maximum standardized uptake value (SUVmax) ranged from 5 to 40. Mediastinal lymph node metastasis was the most common while bone metastasis, liver metastasis, and brain metastasis occured as well. In patients with central lung masses, rapid disease progression, and poor response to initial treatment, the possibility of NUT cancer should be considered and anti-NUT monoclonal antibody immunohistochemical staining, combined with genetic detection, if necessary, should be performed as soon as possible. CT and PET/CT imaging are essential for the staging, management, treatment response assessment, and monitoring of pulmonary NUT cancer.